Heart Rate and Breathing Are Not Always in Phase During Resonance Frequency Breathing - Lehrer, Paul M.; Vaschillo, Evgeny G.; Vidali, Vinay (Applied psychophysiology and biofeedback, 2020)
For many years it has been an axiom among practitioners of heart rate variability biofeedback that heart rate and breathing vary in phase with each other when people do resonance frequency breathing. When people breathe at the frequency of the baroreflex system, about 0.1 Hz, heart rate and blood pressure have been found to oscillate 180° out of phase, while heart rate and breathing are in phase (zero-degree phase). Thus breathing stimulates the baroreflex by augmenting the baroreflex response with each breath, an effect that is magnified by resonance properties in the baroreflex system. The original data on these relationships came from a study of highly athletic healthy young people. To test this relationship we analyzed phase relationship data between cardiac interbeat interval and breathing during 5-min periods of resonance frequency breathing among 24 adults from a recent study of heart rate variability biofeedback to treat adults with mild to moderate currently symptomatic asthma, ages between 18 and 70. For the specific frequency near 0.1 Hz with the highest amplitude of HRV we calculated coherence and phase between cardiac interbeat interval (IBI) and the respiration curve using the WinCPRS program. Among records with coherence > 0.8, we found a phase relationship of 109° rather than the expected 180°, with IBI changes leading breathing. We computed Spearman correlation coefficients between phase and various subject characteristics, including age, gender, height, and asthma severity. We found no relationship between phase and gender, height, or asthma physiology or symptoms. However, when controlled for gender and height, we found a moderate size significant correlation between phase and age, with younger participants having values closer to 180°, r = 0.47, p < 0.03. It is possible that cardiovascular characteristics of older people affect the phase relationship. Despite the deviation from the in-phase relationship among older individuals, breathing nevertheless stimulated the baroreflex and produced high-amplitude heart rate oscillations. Implications are discussed for HRV biofeedback training protocols. Replication in a healthy population is needed in order to determine the universality of these findings.